Video Development of Learning to Write Short Text for Class XI Students of Tahfizd Asy Syadzili Pakis Malang - Marwani Marwani; Sri Wahyuni; Luluk Sri Agus (Budapest International Research and Critics University, 2022)
Research on the development of learning videos on short story writing material for class XI SMA Tahfizd Asy Syadzili Pakis Malang, researchers used six data collection instruments, and data collection techniques with interviews and distributing questionnaires to students. The results obtained based on teacher interview assessments were 3.67%. And categorized as good and very worthy without comments from experts. Based on the student needs analysis table data, the average score of all aspects is 3.67% or good category. It can be concluded from the data that there is a need for students to get answers according to what is expected and the needs of students. So it can be said that this short story learning video is said to be very feasible to be applied in schools.